1989
DOI: 10.1021/jf00086a032
|View full text |Cite
|
Sign up to set email alerts
|

Volatile components of bittermelon

Abstract: 7-dodecalactone, the yeast reduction product is nearly optically pure and (4ff)-configurated (Gessner et al., 1987).For the case of 3,4-dimethyl 7-lactone the odor activity depends on geometric as well as optical isomerism (Table VI). The (4S)-configurated isomer is much more intense as the (4f?)-isomer in both the cis and trans series. This means that chirality is of special importance for odor intensity. On the other hand, odor quality seems to be mainly influenced by geometric isomerism. While the odor qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…1‐Tridecanol was predominant followed by phytol in the volatiles of Momordica charantia L. (bitter gourd) plants, and geraniol, 1‐tridecanol, and phytol attracted Epilachna dodecastigma Wiedemann beetles (Sarkar et al., ). The major VOCs emitted by fruit and vines of bitter gourd have been found to contain myrtenol, ( Z )‐3‐hexenol, benzyl alcohol, 1‐penten‐3‐ol, ( Z )‐2‐pentenol, ( E )‐2‐hexenal, and cis ‐sabinol, and these volatiles elicited attraction of the fly Dacus cucurbitae (Coquillett) (Binder et al., ). Linalool, 2‐aminobenzaldehyde, 1H‐indole and methyl anthranilate were the most abundant compounds accounting for 95% of the volatiles of M. charantia flowers (Fernando & Grün, ), but those compounds were not detected in volatiles of M. charantia plants.…”
Section: Discussionmentioning
confidence: 99%
“…1‐Tridecanol was predominant followed by phytol in the volatiles of Momordica charantia L. (bitter gourd) plants, and geraniol, 1‐tridecanol, and phytol attracted Epilachna dodecastigma Wiedemann beetles (Sarkar et al., ). The major VOCs emitted by fruit and vines of bitter gourd have been found to contain myrtenol, ( Z )‐3‐hexenol, benzyl alcohol, 1‐penten‐3‐ol, ( Z )‐2‐pentenol, ( E )‐2‐hexenal, and cis ‐sabinol, and these volatiles elicited attraction of the fly Dacus cucurbitae (Coquillett) (Binder et al., ). Linalool, 2‐aminobenzaldehyde, 1H‐indole and methyl anthranilate were the most abundant compounds accounting for 95% of the volatiles of M. charantia flowers (Fernando & Grün, ), but those compounds were not detected in volatiles of M. charantia plants.…”
Section: Discussionmentioning
confidence: 99%
“…One of these, (E)-6-nonenyl acetate, attracts female melon flies (Jacobson et al 1971) as well as stimulates oviposition (Keiser et al 1973). Other compounds, including (Z)-3-hexen-1-ol and E2-6:al, are prominent in extracts of bittermelon, Momordica charantia L., and attract B. cucurbitae (Binder et al 1989). …”
Section: Discussionmentioning
confidence: 99%
“…Numerous aldehydes have been reported in other Cucurbitaceae such as bittermelon (Momoridica charantia L.), cucumber (Cucumis sativus L.), and watermelon (Citrullus lanatus Thunb.) (Binder et al, 1989;Fleming et al, 1968;Yajima et al, 1985); and (Z)-3-hexenal and (E)-2-hexenal were attributed to the "green notes" in C. melo (Schieberle et al, 1990). In year-1, four scientists observed that only immature cantaloupe (13 and 20 DAA) smelled and tasted like cucumber.…”
Section: Volatile Trends In Immature Fruitmentioning
confidence: 99%